2003
DOI: 10.1080/0020772131000158500
|View full text |Cite
|
Sign up to set email alerts
|

Economic Order Quantity model with Weibull deterioration distribution, shortage and ramp-type demand

Abstract: A single-item single-period Economic Order Quantity model for deteriorating items with a ramp-type demand and Weibull deterioration distribution is considered. The shortages in inventory are allowed and backlogged completely. The model is developed over an infinite planning horizon and the optimal replenishment policy is derived by minimizing the total inventory cost per unit time. The numerical solution of the model is obtained, and the sensitivity of the parameters involved in the model is also examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(51 citation statements)
references
References 18 publications
0
51
0
Order By: Relevance
“…Deng et al (2007) focussed on the doubtful results found by Mandal and Pal (1998) and Wu and Ouyang (2000) and obtained a more consistent solution. Panda et al (2008Panda et al ( , 2009 extended Giri et al's (2003) one-fold demand model to two-fold demand. Model studied by Hill (1995) was extended to trapezoidal-type demand rate by Cheng and Wang (2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al (2007) focussed on the doubtful results found by Mandal and Pal (1998) and Wu and Ouyang (2000) and obtained a more consistent solution. Panda et al (2008Panda et al ( , 2009 extended Giri et al's (2003) one-fold demand model to two-fold demand. Model studied by Hill (1995) was extended to trapezoidal-type demand rate by Cheng and Wang (2009).…”
Section: Introductionmentioning
confidence: 99%
“…After that, Wu (2001) developed a model for deteriorating items with ramp-type demand and partial backlogging. Giri et al (2003) extended ramp-type demand inventory model with more general Weibull distribution deterioration rate. Manna and Chaudhuri (2006) studied an EPQ model with ramp-type two time periods categorized demand pattern assuming demand dependent production.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration rate of the items is directly proportional to the maximum life time, which may be controlled the maximum life time of the produced items. An inventory model with shortage, ramp-type demand rate and time dependent deterioration rate was discussed by Giri et al (2003). Manna and Chaudhuri (2006) introduced an EOQ model for items with deterioration and time-dependent demand.…”
Section: Introductionmentioning
confidence: 99%
“…Wu (2001) investigated an inventory model with ramp type demand rate, Weibull distributed deterioration rate and partial backlogging. Giri et al (2003) extended the ramp type demand inventory model with a more generalized Weibull deterioration distribution. Deng et al (2007) revisit the inventory model considered by Mandal and Pal (1998) and Wu and Ouyang (2000).…”
Section: Introductionmentioning
confidence: 99%